Penggunaan Led Grow Light dalam Pengembangan Media Pembelajaran Simulator Hidroponik Mini Berbasis Mikrokontroler di SMK Pertanian - Jamaluddin Jamaluddin; Amirah Mustarin; Ervi Novitasari (Seminar Nasional LP2M UNM, 2019)
The research aims to develop media, validity and see students' responses to the application of mini hydroponics simulator learning media based on microcontrollers with the addition of LED grow lights in SMK. The type of research used is research development (Research and Development). Efforts to develop instructional media to meet the needs of students at the vocational level, it is necessary to flow the research process using the ADDIE development model, covering 5 stages in its implementation, namely analysis, design, development, implementation, and evaluation . The object of the research is a mini hydroponic simulator based on a microcontroller with the addition of led gow light which has been validated by media and material experts. Validation by media experts is carried out to assess and provide input to the media and validation by material experts is carried out to assess and provide input to the media usage manual. The research respondents consisted of 25 students. The instrument used for data collection was the use of a questionnaire. The measurement scale of the data uses a Likert scale and the activity of data analysis is done by finding the percentage (%) of validity and response of students. The results showed that the development of the simulator included the addition of led grow light components, light sensors, active buzzers and a more flexible construction. Through the application of simulators, students gain new knowledge about more modern hydroponic cultivation. Simulator validation conducted by media experts obtained a percentage value of 92%, which means that it was very valid to be used, while the validation of the manual that was done by material experts obtained a percentage value of 94.1%, which means it was very valid. Student responses to the simulator showed a percentage of 87.25% which means there is a very positive response to the application of the simulator in the learning process.